SOCIAL MOVEMENTS IN PROMOTING ENVIRONMENTAL AWARENESS: ZERO WASTE CAMPAIGN STUDY - Sandy, Masri Ramadilla; Fatimah, Fatimah (LPPM Universitas Bina Bangsa, 2025)
The aim of this research is to describe social movements in encouraging environmental awareness: a study of zero waste campaigns using a literature approach. The method used is a descriptive method with a literature approach, by analyzing 50 international and national journals that have been published online. Before the paper is published, it must first be discussed with peers and colleagues to get meaningful input. After the paper has been revised according to colleagues' input, the paper is published to increase the scope of scientific development. Increasingly complex environmental problems, especially those related to increasing waste volumes, require an approach that is not only technical, but also social. Social movements are an effective strategy in forming society's collective awareness of environmental issues. This research aims to examine the role of social movements, particularly through zero waste campaigns, in encouraging awareness and changing people's behavior towards a sustainable lifestyle. The method used is a literature study with analysis of various journals and activity reports related to zero waste campaigns in various regions. The results of the study show that the zero waste campaign is able to increase public understanding of waste management, encourage changes in consumption and production patterns, and open up opportunities for innovation based on a circular economy. However, implementation in the field still faces challenges such as limited facilities, uneven education, and lack of policy support. Therefore, synergy between actors, from society, community, to government, is the key to strengthening this movement in a sustainable manner.